Continuous Zeolite MFI Membranes Fabricated from 2D MFI Nanosheets on Ceramic Hollow Fibers. (8th May 2019) - Min, Byunghyun; Yang, Shaowei; Korde, Akshay; Kwon, Yeon Hye; Jones, Christopher W.; Nair, Sankar
Abstract: High‐quality 2D MFI nanosheet coatings were prepared on α‐alumina hollow fiber supports by vacuum filtration and then transformed into molecular sieving membranes by two sequential hydrothermal treatments. This processing method eliminates the need for specially engineered silica‐based support materials that have so far been necessary to allow the formation of functional membranes from 2D MFI nanosheets. The sequential steps enhance adhesion of the membrane on the fiber support, fill in nanoscale gaps between the 2D nanosheets, and preserve the desirable (0 k 0) out‐of‐plane orientation without the need of any support engineering or modification. The membrane exhibits high performance for separation of n ‐butane from i ‐butane, and for other technologically important hydrocarbon separations. The present findings have strong implications on strategies for obtaining thin, highly selective zeolite membranes from 2D zeolites in a technologically scalable manner. Abstract : Dünn und ausgerichtet : Dünne, hoch (0 k 0)‐orientierte Zeolith‐MFI‐Membranen wurden auf keramischen Hohlfasern hergestellt, ausgehend von der Beschichtung mit 2D‐MFI‐Nanoblättchen sowie nachfolgenden sekundären und tertiären Hydrothermalbehandlungen. Die Membranen sind in der Lage, Butanisomere und Gaskondensat‐Komponenten effizient von Methan zu trennen.